Right to the City: The Forum of Public Policy Councils' experience in the interior of Minas Gerais - Batista Corrêa da Costa, Márcia Helena; Meire Guimarães, Sandra; Castro, Bruna Laís (Guará Journal, 2018)
The  experience  reported  in  this  article  was developed from  the  articu-lation between research and university extension, having as object the project "Political Participation and Right to the City". The central objective was  to  create  situations  of  interlocution  of  the University  with  the  organized  social  segments,  acting in  Councils  and  other  modalities  of  associativism, with a view to favoring the understanding of these actors on  the  right  to  the  city.  The  reference  of  the discussions  was  the  Urban  Reform present in Law n. 10.257 / 2001, the City Statute (ver a observação acima, neste caso acrescentar a conjunção se for outra obra), in order to promote  the  maturation  of  channels  for dialogue  between  civil  society  and local public authorities, stimulating processes of political participa-tion  aimed  at  consolidating  the  democratic management  instruments  of the city. The activities developed were successful, however, the depen-dence of these instances on the executive power impaired the continuity of  actions  and  the  autonomy  sought  for the  councils  in  the  conception  and social control of policies.
Keywords: Political participation; Right to the city; Public policies